When Jack Blinks: Si(gh)ting gay desire in Ann Bannon's Beebo Brinker - Barale, Michèle Aina (Feminist studies, college park, 1992)
The overtly lesbian story, "Beebo Brinker," by Ann Bannon offers the heterosexual male reader an opportunity to engage in nonheterosexual imaginings. Bannon's story is examined for its subcultural appropriation and subversion as a crossover novel in reverse.
Keywords: approches et analyses; arts; discipline; hétérosexisme; identités LGBTQIA2+; lesbianisme; ressource en ligne; systèmes d'oppressions; études littéraires

New lesbian criticism: Literary and cultural readings - Munt, Sally (Between men-between women, 1992)
This volume explores whether there can be a specific lesbian aesthetic, juxtaposed against reading as a woman´ or as a heterosexual´. Contributors both explore the uses of recent theories such as post-structuralism and offer a lesbian critique of such methodologies. Close readings of contemporary lesbian fiction and popular culture focus on works such as Zami, Oranges Are Not the Only Fruit, The Wanderground, and Desert of the Heart as well as on lesbian pornography. Together the essays point to lesbian culture´s ability to create new meanings for iteself and to foreground the intertextuality of lesbian identities. Contributors: Sonya Andemahr, Lisa Henderson, Hilary Hinds, Katie King, Reina Lewis, Sally Munt, Gillian Spraggs, Angela Weir, Anna Wilson, Elizabeth Wilson, and Bonnie Zimmerman.
Keywords: 1900-1999; approches et analyses; arts; discipline; hétérosexisme; personnes lesbiennes; périodes historiques; systèmes d'oppressions; études culturelles; études littéraires